2014
DOI: 10.17700/jai.2014.5.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Drivers of Mobile Telephony for Sustainable Livelihood among Rural Farming Households in Kwara State, Nigeria

Abstract: A B S T R A C TRecently, it is acknowledged that mobile phones provide multiple functionalities and diverse applications that affect all forms of capital accumulation, necessary for sustainable livelihood. However, there is no empirical result regarding the impact of mobile phones on asset accumulation in Nigeria. This study examined the socio-economic determinants of mobile phone use and intensity of use for sustainable capital formation in farming households in Kwara state, Nigeria. Accordingly, 120 rural fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In the current study, older people were frequently reluctant to adopt new technologies than the younger ones. This finding is in line with previous studies by Nyamba and Mlozi (2012) in Kilolo District, Iringa, Tanzania, and Animashaun et al (2014) in Kwara, Nigeria which reported that young farmers had higher chances of using mobile phones in accessing agricultural information. Therefore, the use of mobile phone initiatives should take part in educating people of all age groups.…”
Section: Social Demographic Factors Influencing the Use Of Mobile Phones In Accessing Rice Information For Adaptation To Climate Changesupporting
confidence: 92%
“…In the current study, older people were frequently reluctant to adopt new technologies than the younger ones. This finding is in line with previous studies by Nyamba and Mlozi (2012) in Kilolo District, Iringa, Tanzania, and Animashaun et al (2014) in Kwara, Nigeria which reported that young farmers had higher chances of using mobile phones in accessing agricultural information. Therefore, the use of mobile phone initiatives should take part in educating people of all age groups.…”
Section: Social Demographic Factors Influencing the Use Of Mobile Phones In Accessing Rice Information For Adaptation To Climate Changesupporting
confidence: 92%
“…Equal access to internet and information services is today a necessity as most services go online. As such, the technology has been viewed as a remedy to the social economic problems [31]; [32] in both developing and developed world's societies [19]; [20]. There has been a major emphasis on the link between broadband infrastructure and economic growth by developed Governments [33].…”
Section: Othersmentioning
confidence: 99%
“…This is relevant because getting the right information, when and where needed, in a language understood and can be easily accessed are recognized as vital to the success of the agricultural sector as the right type of soil, adequate water, sunlight and any other input. Integration into the value chain therefore, poses an increasing challenge to resource-poor producers when asymmetries occur in access to information among stakeholders (Animashaun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%